Life at Rock Surfaces Challenged by Extreme Light, Temperature and Hydration Fluctuations - Büdel, Burkhard; Büdel, Burkhard; Büdel, Burkhard; Büdel, Burkhard; Coleine, Claudia; Coleine, Claudia; Cowan, Don A.; Cowan, Don A.; Darienko, Tatyana; Darienko, Tatyana; Friedl, Thomas; Friedl, Thomas; et al. (Life in extreme environments ;, 2021)
Rock surfaces provide a challenging habitat for a broad diversity of micro- or small-sized organisms. They interact with each other forming complex communities as well with their substrate causing biodeterioration of rock. Extreme fluctuation in light, temperature and hydration are the main factors that determine the rock surface habitats. The habitat includes epilithic organisms which thrive on the surface without penetrating the rock, endolithic organisms which live just beneath the surface using a thin layer of the rock surface for protection against adverse conditions of the environment (e.g. light protection, storage of water) and chasmo-endolithic organisms which use fractures of the rock surface for a more habitable environment. The book will provide an overview of the various organismal groups, from prokaryotes to vascular plants and arthropods, as well as survey organism-mediated interactions with the rock surface. The latter include biogenic weathering (biogeochemistry, state-of-the art imaging methods), photosynthesis and nitrogen fixation at and inside the rock surface.